سفينة النجا Safīnah al-Najā: Al-Shaykh Salim bin Abdullah bin Sumair Al-Hadrami Al-Syafi'i - Zulkefli, Ahmad Arif; Mohamad Sabari, Mohamad Firdaus; al-Akiti, Muhammad Ayman (ARG Training & Consultancy, 2020)
Terjemahan, Syarahan dan Baht al-Masa'il oleh Dr. Ahmad Arif bin Zulkefli dan Ustaz Mohamad Firdaus bin Mohamad Sabari